2021
DOI: 10.3389/fped.2021.771750
|View full text |Cite
|
Sign up to set email alerts
|

Reference Interval for Pulse Oxygen Saturation in Neonates at Different Altitudes: A Systematic Review

Abstract: Introduction: The reference interval for pulse oxygen saturation (SpO2) in neonates born at high altitudes has not been defined to date. The purpose of this study was to systematically review published studies and determine the reference interval of SpO2 in neonates at different altitudes.Methods: Databases of PubMed, Embase, Cochrane Library, Clinicaltrials.Gov, Chinese National Knowledge Infrastructure Database, Wanfang Database, Chinese Science Technology Journals Database, and Chinese Clinical Trial Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, this is the first multicentre investigation of SpO 2 reference interval in healthy neonates 24 hours after birth at high altitudes. We will establish a prediction equation to address the inability to establish a uniform reference interval because of the curvilinear decrease in the lower limit value of the SpO 2 reference interval with the increase in altitude 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this is the first multicentre investigation of SpO 2 reference interval in healthy neonates 24 hours after birth at high altitudes. We will establish a prediction equation to address the inability to establish a uniform reference interval because of the curvilinear decrease in the lower limit value of the SpO 2 reference interval with the increase in altitude 16…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found only a few reports on the SpO 2 of neonates 24 hours after birth in areas above 2000 m. We also noted that while these previous studies used the mean±SD to describe the results, their mean+2 SD exceeded the theoretical maximum of 100%, indicating that their results were not normally distributed 16. IQRs should have been used so that reliable reference intervals could be derived.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Such knowledge is crucial for both critical congenital heart disease (CCHD) screening and appropriate oxygen therapy to avoid hyperoxia-related risk from excess use of supplemental oxygen [ 2 , 3 ]. However, the data are scarce and are compounded by the different physiologic adaptations between newborns at higher altitudes and those at sea level [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%